Web-based student evaluation of instruction - Nayani, Radhika (My University, 2010)
Student Evaluation of Instruction (SEI) is a survey instrument for collecting student feedback on the quality of instruction. In University of Wisconsin-La Crosse (hereafter referred to as the "UWL"), feedback from students is usually gathered through paper-based questionnaires. Such surveys consist of a standard set of questions addressing general aspects of teaching that involves both instructor and course. Student evaluation of teaching is important to the university for two primary reasons. First, student evaluations provide data used for administrative decisions such as tenure, promotion, and salary increases for faculty. Second, teaching evaluations provide feedback to help faculty improve teaching performance. There are several advantages of using an online system when compared to paper based evaluation; some of the important advantages include increased efficiency in data collection process, flexibility of questionnaire design, eco-friendly avoidance of paper wastage and immediate availability of data for analysis and reporting. The current process involves the great deal of labor to handle the student's anonymity. The project described in this report is called "Online Student Evaluation of Instruction" (hereafter referred to as the "SEI"); it is a web-based system developed to collect teaching evaluation data for summative and formative purposes. The evaluations will be administered and collected in a manner that assures security. It addition, reports will be delivered in a timely fashion to administrators in a manner that is easy to understand and interpret. The OSEI system has been designed to allow flexibility in changing the questions, reports and evaluations.
Keywords: Web site development.; Student evaluation of teachers -- Software.; College teaching -- Evaluation -- Software.; University of Wisconsin--La Crosse -- Evaluation.